ANALISIS RISIKO PRODUKSI USAHATANI JERUK SIAM PONTIANAK (Citrus nobilis var. Microcarpa) DI KABUPATEN SAMBAS (Jurnal Social Economic of Agriculture, 2017)
Agricultural risks are a serious matter faced byfarmers. The objectivesof this studywere to 1) Analysis input factors that influence the production of jeruksiam farming in Kabupaten Sambas, 2) Analysis input factors that influence the production risk of jeruksiam farming in Kabupaten Sambas.  This research was a survey research to 100 farmers or jeruksiam in KecamatanTebasKabupaten Sambas. Qualitative analysis used to describe situation or phenomena of the research. Quantitative analysis used to analyze production and production risk through Just and Pope approach based on Cobb-Douglas production function model. This model examined by classical assumption test (multicollinearity and heteroscedastic) then examined with R2test, F-test, and t-test. The results showed that production inputs with positive coefficients increase production of jeruksiam such as land area (0.205), numbers of plant (0.504), Urea (0.573) andpesticide (0.064). But t-test showed that only numbers of plantand Urea that have real influence to the production of jeruksiam (p-value < 5%).